Determination of thermal and mechanical material properties if ultra high strength steels for hot stamping - Lechler, Jürgen; Merklein, Marion; Geiger, Manfred (Steel Research International, 2008)
Direct and indirect hot stamping presently constitutes one of the most innovative forming technologies in the automotive industry through the combination of forming and hardening in one process step or line. Thus, structural components with strength up to 1600 MPa can be accomplished with the quench hardenable ultra-high strength steel 22MnB5. With respect to the numerical investigation of the feasibility of different parts the knowledge of various thermal and mechanical material characteristics determined under process relevant conditions are required. Within the scope of this paper different experimental methods will be introduced for the determination of material properties according to the typical time-temperature characteristics of the hot stamping process, as well as the modelling of it as input data for the FE analysis.
LFT Import::2019-07-29 (1561)
Keywords: 22MnB5; Flow behaviour; Heat transfer; Hot stamping; Modelling